A systematic review of the correspondence between descriptive assessment and functional analysis. Issue 1 (21st November 2022) - Contreras, Bethany P.; Tate, Savannah A.; Morris, Samuel L.; Kahng, SungWoo
Abstract : Clinicians report that they often rely on descriptive assessments when developing behavior‐reduction plans despite literature suggesting that functional analysis is the most rigorous assessment method. Further, research comparing the outcomes of descriptive assessments and functional analyses is mixed, with some studies showing low correspondence and others showing high correspondence. Such persistent use of descriptive assessments suggests that they may yield useful information despite inconsistent correspondence with functional analyses. A more fine‐grained analysis of the relation between descriptive assessments and functional analyses may elucidate variables affecting their utility. We conducted a review of 48 studies that included descriptive assessments and functional analyses and evaluated several measures of correspondence between each pair of assessments. Results indicated that descriptive assessments had exact correspondence with functional analyses in 50% of comparisons. Results also suggested that descriptive assessments were more likely to accurately identify and predict the absence of a function relative to the presence of a function and that structured descriptive assessments were more likely to accurately predict functions.